Boundary vector cells in the goldfish central telencephalon encode spatial information - Cohen, Lear; Vinepinsky, Ehud; Donchin, Opher; Segev, Ronen (PLOS Biology, 2023)
This study identifies a new building block in the navigation system of fish: boundary vector cells in the central telencephalon of goldfish enable a unique encoding of position, documented here for the first time in the largest group of vertebrates.